FIQH CAGAR BUDAYA: REKONSTRUKSI FIQH ISLAM DALAM BINGKAI PERADABAN NUSANTARA - Misno Mohammad Djahri (Institut Agama Islam Sahid Bogor, 2020)
Indonesia is a vast nation which has abundant cultural heritage, the effort to preserve it had been done to protect the cultural heritage. However, damage to the cultural heritage objects continue to occur. One reason is because of religious elements. Worry makes people commit shirk is one reason. Damage to objects of cultural heritage took place in Muslim countries for the same reason, Iraq, Syria, Afghanistan and Saudi Arabia is a country with a high damage cultural heritage. How Islam regards the protection of cultural heritage? Fiqh as an element of Islamic law has a dynamic and flexible nature, one of the very nature is friendly to tradition and culture. The concept of fiqh Nusantara provides solutions in damage to the cultural heritage objects. The legal basis for the protection of cultural heritage is; customs and 'urf Muslims in Indonesia, kindness, collective ijtihad and deductive analogy. Finally fiqh cultural heritage is an element of Islamic law that protects objects of cultural heritage.